Pengaruh Motivasi Kerja dan Iklim Kerja Terhadap Kepuasan Kerja dan Implikasinya Terhadap Kinerja Tenaga Kependidikan Institut Pertanian Bogor - Diyanti Diyanti; Musa Hubeis; M. Joko Affandi (School of Business, Bogor Agricultural University (SB-IPB), 2017)
Bogor Agricultural University supporting staff (known as tenaga kependidikan or tendik) is one of the Human Resources (HR) that have a strategic role in providing excellent services to the students and lectures. Therefore they need to have an adequate competence. Objective of this research is (1) analyze the influence of work motivation toward job satisfaction of supporting staff, (2) analyze the influence of work climate toward job satisfaction of supporting staff and, (3) analyze the influence job satisfaction toward of supporting staff’s performance in Bogor Agricultural University. Based on SEM-PLS analysis, it was known that work motivation and work climate significantly affected job satisfaction. Furthermore, job satisfaction significantly affected by the supporting staff performance in Bogor Agricultural University. In addition, R-Square value for job satisfaction was 0.458. It means that work motivation and work climate has contributed positively to the satisfaction as much as 45.8%, and the rest 54.2% was influenced by other factors. Furthermore, R-Square value for Supporting staff performan was 0.028. it means that supporting staff performance was positively influenced by job satisfaction as much as 2.8%, and the rest 97.2% was influenced by other factors.Keywords: climate, supporting staff, work motivation, supporting staff, SEMAbstrak: Tenaga Kependidikan (Tendik) Institut Pertanian Bogor (IPB) sebagai salah satu Sumber Daya Manusia (SDM) yang memiliki peran strategik dalam memberikan pelayanan, baik kepada mahasiswa maupun dosen perlu memiliki kompetensi memadai. Penelitian ini bertujuan (1) menganalisis pengaruh motivasi kerja terhadap kepuasan kerja Tendik, (2) menganalisis pengaruh iklim kerja terhadap kepuasan kerja Tendik, dan (3) menganalisis pengaruh kepuasan kerja terhadap kinerja Tendik IPB. Berdasarkan analisis SEM-PLS, diketahui bahwa motivasi kerja dan iklim berpengaruh nyata terhadap kepuasan kerja Tendik IPB, kepuasan kerja berpengaruh terhadap kinerja Tendik. Nilai R-Square untuk kepuasan adalah 0,458. Artinya, motivasi kerja dan iklim kerja mempunyai kontribusi positif terhadap kepuasan 45,8 % dan 54,2% dipengaruhi oleh faktor lain. Selanjutnya, nilai R-Square untuk kinerja Tendik IPB adalah 0,028. Artinya, kinerja Tendik IPB dipengaruhi secara positif oleh kepuasan kerja sebesar 2,8% dan 97,2 % dipengaruhi oleh faktor lain.Kata kunci: iklim kerja, kepuasan kerja, motivasi kerja, tenaga kependidikan, SEM